A Critical Discourse Analysis of David Crystal’s Views on the Globalization of English - Subhasingha, S.A.K.M. (University of Jaffna, 2025)
The globalization of English refers to the widespread use of English across nations and cultures beyond its native speakers. It involves the language’s adoption in various domains, from international business and diplomacy to education and popular culture, leading to its status as a lingua franca. David Crystal, a renowned British linguist, is a leading figure in the study of the English language. Crystal’s extensive work on language evolution, usage, and globalization makes him a crucial voice in discussions about English’s global status. Analysing his perspectives is vital for gaining informed insights into the past, present, and future of English in a globalized world. Despite the extensive research on English as a global language, there remains a lack of critical engagement with the ideological positioning of influential linguists like David Crystal. While many studies focus on the spread and utility of English, few interrogate the implicit assumptions and power dynamics in expert narratives. This study aims to critically examine Crystal’s predictions regarding the future of English through the lens of discourse and power. Based on its aim, this research looks forward to answer the research question of “What are Crystal’s predictions regarding the future of English as a global language?” This study employs a qualitative research design, using Fairclough’s three-dimensional model of critical discourse analysis as its theoretical framework. This model allows for a systematic examination of the interview text, considering its linguistic features, discursive practices, and socio-cultural context. The data source is a YouTube interview with David Crystal titled “Will English Always Be the Global Language?” selected through purposive sampling due to its relevance to the research topic. The interview was transcribed verbatim and then coded thematically to identify key themes and patterns related to the globalization of English. The analysis of Crystal’s interview reveals not only his emphasis on historical and political forces such as British colonialism and American influence but also his framing of English as a naturally dominant language. This perspective, while informative, subtly reinforces the notion that English deserves its global role. Through Fairclough’s model, this study reveals how such framing reflects and sustains linguistic hierarchies. For example, Crystal’s cautionary remarks on Mandarin suggest an awareness of global shifts, yet his tone implies confidence in English’s continued dominance.This contradiction highlights the ideological work being done through seemingly neutral commentary. This study does not merely summarize Crystal’s views, it critiques them. By treating expert discourse itself as a subject of analysis, this research contributes an original perspective to ongoing debates around decolonizing English. It demonstrates how dominant narratives, even from respected scholars, can subtly reproduce global power imbalances. Future studies might benefit from comparing such discourse with counter-narratives emerging from the Globalization.
Keywords: Critical discourse analysis; David Crystal; English as a Lingua Franca; Fairclough’s three dimensional model; Globalization of English